Min-Max Simulation: An Execution Design of Process Scheduling Algorithm - Sukhija, Karan (International Journal of Computer Sciences and Engineering, 2025)
Job scheduling is an elementary characteristic of an operating system. The perception is to have system resources shared by a number of processes. A number of steps need to be performed to execute a program. Instructions and data must be loaded into main memory, I/O devices and files must be initialized, and other resources must be prepared. The efficiency of a system solely is subject to the use of job scheduling algorithm in a multi-programmed system. This paper begins with a brief representation of task or job sets, followed by a discussion about different type of job scheduling algorithms. In addition, the elaboration of comparative study of the entire scheduling algorithm along with proposed work is also given. This manuscript represents the simulation design of proposed CPU scheduling algorithm called MIN-MAX which is both preemptive and non-preemptive in nature. This work encompasses a software tool which produces a wide-ranging simulation of a number of CPU scheduling algorithms and provides the output in the form of scheduling performance metrics. The main objective of the paper is to analyze the performance of different algorithms with the proposed algorithm that results in minimum average waiting time and context switches. The major focus is to improve the system efficiency in multi programming system and also reduces the starvation problem among minimum and maximum burst time processes.